Pengaturan Layanan Izin Tinggal bagi Warga Negara Asing - Umbu Kudu Katauhi Mila; Josef Mario Monteiro; Cyrilius W.T. Lamataro (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to analyze the regulation of residence permit services for foreign citizens after the stipulation of the regulation of the Minister of Law and Human Rights number 22 of 2023 concerning visas and residence permits. This research is a normative research supported by field research and literature research using primary legal materials, secondary legal materials and tertiary legal materials collected using documentation techniques or literature studies and processed and analyzed in a qualitative descriptive manner. The results of the study show that (1) Synchronization of foreigner residence permit arrangements between Law Number 6 of 2011 concerning Immigration, Government Regulation Number 31 of 2013 concerning Implementation Regulations of Law Number 6 of 2011 concerning Immigration and Regulation of the Minister of Law and Human Rights Number 22 of 2023 concerning Visas and Residence Permits It is important to create legal certainty and the effectiveness of the implementation of rules (2) Factors that cause Foreign Citizens to exceed the limit of Residence Permit in Indonesia, namely Legal Awareness Factors and Legal Compliance Factors.